Decreased circulating levels of angiopoietin – 1 (Ang-1) are associated with the presence of multinodular goiter or differentiated thyroid cancer - Alexander M. Nixon; Xenia Provatopoulou; Eleni Kalogera; Garyfalia Bletsa; George N Zografos; Dimitrios Bouklas; Akrivi Kostopoulou; Anastasios Philippou; Michael Koutsilieris (Surgery in Practice and Science, 2023)
Background: The aim of this study was to investigate whether the presence of benign or malignant nodular thyroid disease affects levels of circulating angiogenesis cytokines. Methods: In this study we investigated levels of angiopoietin – 1 and -2 (Ang-1 and Ang-2 respectively), vascular endothelial growth factor –A (VEGF-A), galectin-3 (Gal-3), urokinase plasminogen activator receptor (uPAR) and plasminogen activation inhibitor – 1 (PAI-1) in 40 patients with differentiated thyroid cancer (DTC), 45 with thyroid papillary microcarcinoma (mPTC), 53 patients with multinodular goiter (MNG) and 58 controls. Six months after surgery 28 patients resubmitted blood samples. The diagnostic value of Ang-1 levels was evaluated with receiver operating characteristic (ROC) curves. Results: Statistically significant lower levels of Ang-1 were observed in DTC and MNG patients compared to controls (p<.05). No significant differences were observed in the levels of the other factors. The area under ROC curves for Ang-1 discerning DTC, mPTC and MNG from control were 0.68, 0.66 and 0.71 respectively. A significant increase in Ang-1 levels (p<.05) was documented in the subset of patients that underwent thyroidectomy. Thyroidectomy did not influence levels of the other factors. Conclusions: Our results suggest an association between low levels of Ang-1 and the presence of underlying benign or malignant nodular thyroid disease.